2015
DOI: 10.1159/000435789
|View full text |Cite
|
Sign up to set email alerts
|

Carriers of Autosomal Recessive Alport Syndrome with Thin Basement Membrane Nephropathy Presenting as Focal Segmental Glomerulosclerosis in Later Life

Abstract: Collagen IV nephropathies (COL4Ns) comprise benign familial microscopic hematuria, thin basement membrane nephropathy (TBMN), X-linked Alport syndrome (AS) and also autosomal recessive and dominant AS. Apart from the X-linked form of AS, which is caused by hemizygous mutations in the COL4A5 gene, the other entities are caused by mutations in the COL4A3 or COL4A4 genes. The diagnosis of these conditions used to be based on clinical and/or histological findings of renal biopsies, but it is the new molecular gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 51 publications
5
63
0
2
Order By: Relevance
“…The phenotypic heterogeneity observed among patients with inherited monogenic disorders, including AS, TBMN and CFHR5 nephropathy, prompted us to hypothesize that the full spectrum of the phenotype behaves as a multifactorial condition, implicating primary genes, modifier genes and environmental factors [34, 37]. Here we considered that excellent candidates to act as genetic modifiers could be non-synonymous SNPs located in specific genes of the SD.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic heterogeneity observed among patients with inherited monogenic disorders, including AS, TBMN and CFHR5 nephropathy, prompted us to hypothesize that the full spectrum of the phenotype behaves as a multifactorial condition, implicating primary genes, modifier genes and environmental factors [34, 37]. Here we considered that excellent candidates to act as genetic modifiers could be non-synonymous SNPs located in specific genes of the SD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence or absence of hematuria may help to distinguish between MDs and Alport’s syndrome. Of note, patients with Alport’s syndrome can present with FSGS on kidney biopsy and therefore, this cannot be used as a feature to distinguish between the two conditions [16, 17]. Mutations in the COL4A3-5 genes that encode α-chains of glomerular basement membrane collage type IV are classically associated with Alport’s syndrome, and recent studies have shown that these mutations can be associated with FSGS [18].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the above-described cases of FSGS should be considered to be familial FSGS or rather a secondary effect of undiagnosed TBMN is a matter of debate 36 . FSGS occurs in at least 5% of patients…”
Section: Truncatingmentioning
confidence: 99%
“…Across disease categories COL4A3-5 FSGS (AD) [33][34][35] FSGS could arise secondary to unrecognized TBMN through complex mechanisms involving cross-talk between components of the glomerular filtration barrier, through defects in the GBM that result in podocyte foot-process effacement and GBM scarring, and through the actions of modifier genes 36,38 TBMN (AD) 122,123 Alport syndrome (AD, AR, XL) 124,125 DGKE MPGN (AR) 39 • aHUS could arise secondary to MPGN and vice versa because loss of DGKE function and complement activation both cause sustained diacylglycerol signalling 39,44 , which induces glomerular epithelial cell injury, proteinuria, upregulation of prothrombotic factors and platelet activation 20,44,46,47 , and increases TRPC6 channel activity, which is associated with podocyte foot-process effacement and nephrotic syndrome 44,48 • In DGKE-mediated aHUS, the main prothrombotic effect is mediated through upregulation of the pro-inflammatory p38-MAPK pathway that causes impaired endothelial cell proliferation and angiogenesis 45 aHUS (AR) [20][21][22]40 TTC21B Ciliopathies (AR) 51 • Most patients with TTC21B-related glomerulopathy reported to date carry biallelic p.Pro209Leu mutations. This mutation has also been identified in patients with nephronophthisis 51-53 • Glomerulopathies could result from TTC21B-mediated alterations in cytoskeletal architecture in mature podocytes, which affects cell size and migration, actin and microtubule networks and cell nucleation 52 • Tubular lesions characteristic of nephronophthisis suggest a concomitant ciliary defect in glomerulopathy patients 52,53 Glomerulopathies (AR) 52,53 PAX2 RCS (AD) 126 • Truncating PAX2 mutations are more frequently associated with RCS, while missense mutations are more frequently associated with isolated CAKUT or FSGS 128 • Location of the mutation within the gene is associated with the phenotype 128 • FSGS could develop secondary to subtle renal developmental anomalies or through dysregulat...…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation